Shear Stress on the Structure Control of a Supported Fly Ash‐Based Catalyst and Its Application in SCR* Denitration. Issue 31 (17th August 2021) - Hao, Shu; Yuling, Liu; Yang, Jia
Abstract: Nitrogen oxides (NOx) are one of the air pollutants, mainly from coal‐fired power plants, industrial furnaces, etc. In order to control NOx, reduce the preparation cost of denitration catalyst. Selective catalytic reduction is currently the most effective and mature technology for removing NOx. In this paper, solid waste fly ash was used as catalyst carrier, shear reactor was used to prepare Mn−Ce/FA catalyst, and successfully applied to SCR denitration. The catalyst was characterized by SEM, XRD, FTIR, XPS. The results showed that the catalyst prepared by shearing had more dispersed active components. When the power was 80 W, time was 20 min, rotation speed was 120 r/min, and the molar ratio of Mn−Ce was 1 : 1, the optimal catalyst was prepared. Under these conditions, the catalyst had the best activity and strong stability, the denitration performance was the best, up to 82.6 % within 30 min. The introduction of SO2 still showed high catalytic activity and stability, and the removal rate reduced to 73.21 %. After SO2 was stopped, the removal rate rebounded to 77.89 %. Also, Mn−Ce/FA catalyst had good cyclability and stability in the denitration process. Abstract : The catalyst preparation mostly adopts the impregnation method, and the impregnation method will cause the phenomenon of uneven impregnation. In this paper, a self‐developed shear reactor is used to prepare a fly ash‐based catalyst with good uniformity under the conditions of stirring power and time. Under these conditions, it has been used in industrial boiler flue gas denitration, and has achieved certain results, and it still maintains high catalytic activity in the presence of SO2 .